Insights into the reaction mechanism of toluene oxidation by isotope dynamic experiment and the kinetics over MCeZr/TiO2 (M = Cu, Mn, Ni, Co and Fe) catalysts. (1st June 2023) - Zhang, Zirui; Hu, Guangtao; Zhao, Chenchen; Wei, Xiaolin; Dou, Baojuan; Liang, Wenjun; Bin, Feng
Highlights: Ea of intermediate species is calculated during toluene oxidation. Relationship between the activation energy of the overall and primitive reaction. Transient response experiments of isotopically labeled oxygen. M−K mechanism dominates in the oxidation of toluene. Abstract: Catalytic properties of multiple metals deposited on TiO2 nanoparticles were investigated in the oxidation of toluene. Isovolume impregnation method prepared the catalysts containing Cu, Mn, Ni, Co, and Fe deposited on TiO2, including CeO2 and ZrO2 . The effects of loaded metal oxides on the structure and activity of initial catalysts were investigated using various characterization techniques. Toluene's removal efficiency and CO2 selectivity in the catalyst system were classified as follows: CuCeZr/T > MnCeZr/T > NiCeZr/T > CoCeZr/T > FeCeZr/T. Presence of water vapor exhibits an inhibitory effect on the conversion of toluene, which diminishes at higher temperatures. One contribution of this paper is to obtain the oxidation pathway of toluene and the relationship between the activation energy of all-inclusive and elementary reactions based on the variation of infrared spectrum using Freeman-Carroll method. Another contribution is to clarify the share of Langmuir-Hinshelwood and Mars-van Krevelen mechanisms during the oxidation of toluene over CuCeZr/T catalyst by transient response experiments of isotopically labeled oxygen. These findings provide a feasible method for the design and synthesis of transition metal oxide catalysts for industrial applications.